Metaphoric Conceptualizations of Georgian Cultural and National Identities in Oliver Wardrop’s The Kingdom of Georgia (Journal of Advanced Research in Social Sciences, 2024)
The aspiration of Georgia to be part of the Western Culture has always been an irrevocable vector. Nevertheless, it is of immense importance to discursively scrutinize how Europeans perceive this aspiration. Metaphors possess an inherent capacity to represent cultural values of a society and communicate established or competing worldviews. From this perspective, the choice of metaphors, which is cognitively reinforced, conceptualizes culture-specific and national-emotive attitudes that are ascribed to certain communities. The aim of the present paper is to explore conceptual metaphors that contribute to the representation of Georgian cultural and national identities in the eye of a beholder - Sir Oliver Wardrop, who was a British Diplomat and the United Kingdom’s first Chief Commissioner of Transcaucasia in Georgia in 1919-1920 manifesting his take on Georgian cultural and national characteristic features in his work The Kingdom of Georgia (1888). Corpus linguistic software tool AntConc® is used for generating concordance lists for a qualitative discourse analysis of a verbal milieu of the target lingual units – Georgia and Georgian. The research reveals that Georgian cultural and national identities manifested in the discursive realm through the observer’s lenses, which could be referred to as Georgian cultural and national eye-dentities, possess signaling and meaning sides. The latter reinforces the idea that identities function as discursive signs in the narrative of a beholder. What is more, a meaning side of cultural and national identities expressed via the conceptual metaphors acknowledge the emergence of a reshaped Georgian identity that prepared a foundation for establishing Democratic Republic of Georgia (1918-1921).